A relevância da eficácia individual na dinâmica organizacional – um estudo quantitativo - Pereira, Manuel Joaquim de Sousa (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2017)
The choice of this theme arose from the need to understand the communication management in small and medium-sized enterprises in terms of personal and business dynamics, business performance, the personal reputation, proactivity and business dynamics, learning organization and the motivation and personal leadership. We address in this way, the strategy and organizational change, motivation and individual and business needs with regard to capacity building, employee performance and motivation and continuous improvement of business success. The sample is made up of 388 small and medium-sized companies in mainland Portugal. Thus, the assumption of having a probability sample, and considering a two times the standard deviation confidence interval, ie 95.4%, have their maximum statistical error (P = 50%) of +/- 4, 95 pp We also sought to study the attitude of managers in the face of market orientation, the behaviors of the organization, attitudes and staff retention, customer satisfaction, employee satisfaction, commitment, involvement, reputation and business performance, the recommendation, business indicators and satisfaction in working in organizations. We note as well that the relevant aspects for the performance efficiency of employees we can see that the main factors lie in the positive attitude, self-analysis, self-motivation, goal setting, combined with the ability to generate action comprising the other to be understood in the organization where it operates.